Внутризонное поглощение в одномерных наноструктурах - Пащенко, А. Г.; Ванцан, В. М. (ХНУРЭ, 2010)
The use of nanostructures as an active layer of a photo receiver and solar batteries makes it possible to extend significantly the spectrum of the absorbed radiation. Adoption of the cascade nanostructure solar elements permits to span the spectrum of the solar radiation except the region approximately from 1500 nm and more almost completely. One of the methods of this part of the spectrum application to the nanostructure cascade solar elements to increase their efficiency is the use of the intraband transition of the nanostructure cascades making part of the solar element. The given work is devoted to investigation into the mechanism of the intraband absorption in one-dimension nanostructures used for creation of the nanostructure solar elements cascades.Солнечная фотоэнергетика является одной из самых динамично развивающихся областей энергетики. Фотоэлектрический метод преобразования солнечной энергии в настоящее время признан одним из наиболее перспективных среди методов, используемых в нетрадиционной энергетике и может сыграть значительную роль в ее долгосрочном развитии.
Keywords: солнечная фотоэнергетика; однослойные наноструктуры; гетероструктуры; наногетероструктурные каскадные солнечные элементы